At least three linear regions but not the zinc-finger domain of U1C protein are exposed at the surface of the protein in solution and on the human spliceosomal U1 snRNP particle. - Dumortier, H (1998)
No structural information on U1C protein either in its free state or bound to the spliceosomal U1 small nuclear ribonucleoprotein (snRNP) particle is currently available. Using rabbit antibodies raised against a complete set of 15 U1C overlapping synthetic peptides (16-30 residues long) in different immunochemical tests, linear regions exposed at the surface of free and U1 snRNP-bound U1C were identified. Epitopes within at least three regions spanning residues 31-62, 85-103 and 116-159 were recognized on free and plastic-immobilized recombinant human U1C expressed in Escherichia coli, on in vitro translated U1C protein and on U1C bound to the U1 snRNP particle present in HeLa S100 extract. Using a zinc affinity labeling method, we further showed that the N-terminal U1C peptide containing a zinc-finger motif (peptide 5-34) effectively binds65Zn2+. The N-terminal region of U1C, which is functional in U1 snRNP assembly, is apparently not located at the surface of the U1 snRNP particle.